High-velocity microprojectile mediated DNA delivery into Phaseolus vulgaris callus cells - Eissa Ahmed, E.; Bisztray, Gy.; Velich, I. (International Journal of Horticultural Science, 2000)
We report the method for the establishment of rapidly growing callus cultures of Phaseolus vulgaris and the conditions required for efficient transformation using high velocity microprojectiles and high level of transient gene expression. Using hypocotyl explant and vertical culture on B5 medium with lmg/1 kinetin and 2 mg/1 2,4-D, we can recommend to get a rapidly growing callus from bean which is a good starting material to introduce foreign DNA into bean cells. The GeneBooster particle delivery system was used for the bombardment of bean callus and the Hgm resistance gene (Hgmr) was used as a selectable marker gene. 25mg/I hygromycin (Hgm) concentration was sufficient to kill the control callus. We used the standard physical factors, the appropriate pressure of N2 gas for the bombardment of the callus tissue, the shooting distance and the size of tungsten particles used as microprojectiles. Selective and nonselective tests were made by transferring the healthy green and white calluses, subcultured for 4 months on selective and nonselective medium. Several Hgm resistant calli had been obtained. Selective pressure was maintained over a period of 10 months.